Team cohesion advances in psychological theory, methods and practice - Salas, Eduardo; Vessey, William B.; Estrada, Armando X. (Emerald, 2015)
This volume will document the state-of the-science (and practice) on what contributes to effective team cohesion in complex teams. The volume will contain recent developments on theory-building, methodology and the practice of team cohesion.
Keywords: Teams in the workplace -- Management.; elektronické knihy; electronic books